Teaching Effective Summary-Writing: A Reflection on the Efficacy of Scaffolding - Brian Raftery; Maria Zafonte (Journal of Scholarly Engagement)
First-year college students often struggle with summary writing, especially when summarizing a text that is lengthy or complex. Some students, for example, see summarizing as an activity where “excessive copying” is permitted, putting them at risk for plagiarism (Yoshimura, 2018, p. 2). Other students struggle with summaries because they are not effective at picking out the main ideas in a text (Spirgal & Delaney, 2016). As Frey et al. (2003) note, being able to accurately and efficiently restate another author’s thesis is a necessary skill for research papers and academic writing. Based on Kolb’s experiential learning theory, which posits a four-stage learning cycle consisting of concrete experience, reflective observation, abstract concepts, and active experimentation (Kolb et al., 1999), I incorporated scaffolding techniques into my pedagogical approach to summaries. To improve students’ comprehension of the document’s main points, I asked them to organize it into clusters of paragraphs that focused on the same topic for the same audience. When students finished “clustering” the 30 paragraphs in the court document that we were analyzing (Oregon v. Kinkel, 2002), the essential information came into sharp focus, which enabled them to create summaries that accurately reflected the main points and disregard non-essential information.